Towards nuclear imaging with polynuclear radiotracers : the development of monomeric and dendritic scaffolds for radiometals - Malaza, Siphelele (Department of Chemistry, 2016)
A series of 1,4-diaminobutane poly(propylene amine) (DAB-PPI) dendrimer-based ligands were prepared with the aim of developing ligands that will permit the synthesis of multinuclear technetium-99m (99mTc) radiolabeled complexes. The ligands were synthesized by incorporating N,N-donor atom functionalities, at the periphery of DAB-PPI dendrimers, as potential 99mTc chelates. Monomeric ligands were also synthesized as model compounds to aid with the characterization of macromolecular structures. The first (DAB-G1dendr-(NH2)4) and second (DAB-G2dendr-(NH2)8) generation DAB-PPI peripheral amine end-groups were functionalized using appropriate aldehydes, bearing either 2,2'-bipyridyl or 2-picolylamino entities, via a single step reductive amination reaction. The monomeric and new dendritic ligands were comprehensively characterized using spectroscopic (1H NMR, 13C{1H} NMR, infrared) and analytical techniques (mass spectrometry and elemental analysis). Furthermore, the 2-picolylamino-functionalized ligands were found to be water-soluble, S25 °C = 0.01 mg/μL. A series of non-radioactive ('cold') neutral mononuclear and novel multinuclear dendritic rhenium(I) complexes of the form fac-[Ren(CO)3(N,N-bidentate)Xn] (n = 1, 4 and 8 for monomer, G1 and G2, respectively. X = Cl- or Br-) were prepared and characterized. The complexes with the fac-[Re(CO)3Br] core were synthesized at room temperature using the (Et4N)[Re(CO)3Br3]. One of the 2-picolylamino monomeric complexes, fac-[Re(CO)3(N,N-bidentate)Br], was additionally characterized by X-ray crystallography and the crystallographic structure confirms the facial arrangement of the three CO ligands together with the pseudo octahedral geometry around the metal centre.